A estrutura dinâmica da liturgia à luz do realismo zubiriano e do nº 9 da Redemptionis Sacramentum - Bezerra, João José (2023)
This thesis focuses on the Dynamic Structure of the Liturgy in the light of the thinking of the Basque philosopher Xavier Zubiri (1898-1983) and the Instruction Redemptionis Sacramentum written at the request of Pope John Paul II in 2004. One year after the publication of the Encyclical Ecclesia de Eucharistia (April 17, 2003), Pope John Paul II asked the Discastery for Divine Worship and the Discipline of the Sacraments for an instruction of a normative nature to resolve recurrent abuses during the celebration of the Most Holy Eucharist, which was not the first concern of the encyclical letter other than its theological-pastoral content, despite dealing with some points about the danger that perpetrated abuses can pose not only to the celebration of other sacraments and sacramentals, but mainly, with regard to the celebration of the holy sacrifice of the altar. Both the encyclical letter Ecclesia de Eucharistia and the Instruction Redemptionis Sacramentum, recover and direct all those who take part in this mystery by faith, whether the faithful or those who preside, to rediscover, better understand and celebrate its true foundation, which is the Paschal Mystery of Christ. Both the encyclical letter and the RS instruction point to “overshadowing” and to the loss of the notion of this profound reality and its own dynamism. The abuses perpetrated within the Sacred Liturgy, whether at the time of celebration of the sacramentals of the Church, of the sacraments, especially with regard to the sacrifice of the altar, in an attempt to streamline and make Church celebrations more attractive to the faithful demonstrate clearly that It is extremely urgent to recover a true sense of the reality of the Church's liturgy, and only then will it be possible to understand and celebrate with the admiration and respect that the mystery of our faith demands. It is in this sense that Xavier Zubiri's philosophical thought becomes relevant to our research. For him, the notion of reality is not the result of conceptual statements or ideas that we may have of something real. Concepts and ideas come later. The first moment is the “naked reality” apprehended as it is in and of itself in all its notes and structure that little by little through sentient feeling I proceed to individuate intellectually. Here, feeling is not a mere “capturing” of data that something real can offer, but constitutes the primordial moment of the intellective movement towards the full constitution of the felt reality. However, reality is not what I can conceptualize as thought in classical philosophy, but something that is felt and at the same time understood. Only from that unitary moment of feeling and understanding that one can obtain the concept or idea of something that can change as I feel and understand other notes. In other words, reality is not something ready and finished, but reality under construction (realitas in essendo). This new way of understanding reality for theological reflection in the search for an interface becomes a necessary noological way and a “beam” of light for understanding the reality of the sacred liturgy. Zubirano's thought leads us to understand the reality of the liturgy, not as something ready and finished, or as something rigid and fixed that the mere observation of rubrics and norms is enough, but it is a dynamic reality that "makes and makes up" in and of itself without needing any unnecessary addendum. In a second moment, it leads us to understand that the reality of the liturgy is not a concept or some idea about the grace of God or about the presence of God, but there is the “naked and raw” reality that can be felt and understood progressively through the liturgy. primordial apprehension of reality. In a third moment, when presenting the sentient feeling as a process of human feeling, demonstrating its primordial moment and its ulterior modes, it shows us that the human being is deeply involved in its constitutive totality in the knowledge of any and all reality. Not passive, but conscious, active and pious in the face of any reality that imposes itself on him, especially the reality of the Sacred Liturgy in all its dynamism, structural ritus et preces